Single-cell genetic models to evaluate orphan gene function: The case of QQS regulating carbon and nitrogen allocation - Wang, Lei; Tonsager, Andrew J.; Zheng, Wenguang; Wang, Yingjun; Stessman, Dan; Fang, Wei; Stenback, Kenna E.; Campbell, Alexis; Tanvir, Rezwan; Zhang, Jinjiang; Cothron, Samuel; Wan, Dongli; et al. (Frontiers in Plant Science, 2023)
We demonstrate two synthetic single-cell systems that can be used to better understand how the acquisition of an orphan gene can affect complex phenotypes. The Arabidopsis orphan gene, Qua-Quine Starch (QQS) was previously identified as a regulator of carbon (C) and nitrogen (N) partitioning across multiple plant species. QQS modulates this important biotechnological trait by replacing NF-YB (Nuclear Factor Y, subunit B) in its interaction with NF-YC. In this study, we expand on these prior findings by developing Chlamydomonas reinhardtii and Saccharomyces cerevisiae, to refactor the functional interactions between QQS and NF-Y subunits to affect modulations in C and N allocation. Expression of QQS in C. reinhardtii modulates C (i.e., starch) and N (i.e., protein) allocation by affecting interactions between NF-YC and NF-YB subunits. Studies in S. cerevisiae revealed similar functional interactions between QQS and the NF-YC homolog (HAP5), modulating C (i.e., glycogen) and N (i.e., protein) allocation. However, in S. cerevisiae both the NF-YA (HAP2) and NF-YB (HAP3) homologs appear to have redundant functions to enable QQS and HAP5 to affect C and N allocation. The genetically tractable systems that we have developed exhibit the plasticity to modulate highly complex phenotypes.